Digital manufacturing revolutions as political projects and hypes: Evidences from the auto sector - Tommaso Pardi; Martin Krzywdzinski; Boy Luethje (International Labour Organization (ILO), 2020)
The article analyses the evolution of automotive manufacturing technologies and organisations and assesses the impact of "fourth industrial revolution" concepts and policies (in Germany, US and China) in particular for employment and work. While it dismisses the idea that a fourth industrial revolution is under way and that a radical break will happen in the coming years, it shows that more subtle changes are taking place on the shop-floor of automotive factories that might result in deskilling and work intensification. The article advocates for a more active role of trade unions and social partners in challenging these narratives of disruptive change and building alternative human-centred visions of the future of work.
Keywords: 330; employment; industry; motor vehicle industry; technological change; developed countries; developing countries